Meaning or money? Non-profit employee satisfaction. (18th November 2016) - Weisberg, Melinda; Dent, Eric
Abstract : Employees choosing careers with community-based non-profit human services organisations engaged in meeting human needs expecting intrinsic satisfaction often find that the same care and commitment espoused in mission statements are not reflected internally as a commitment to employee satisfaction. These frontline workers are at risk of becoming disillusioned by increasing demands for compliance, internal and external disparities in salaries, unpaid work hours and difficulties in achieving outcomes. Using Herzberg's two-factor theory as a framework, this article incorporates a systematic review of literature per the discipline of evidence-based research to examine the potential of applying non-monetary satisfiers to invigorate the human services workforce. The article, which includes recommendations for management, focuses on the environment for frontline workers and includes creating a flexible workplace as well as implementing best practices for intentionally engaging employees in decision making and problem solving. The article has global relevance for staff retention and job satisfaction issues.